Analysis of Health System Resilience in Response to Emerging Pathogen Outbreaks and Public Health Emergencies of International Concern (PHEIC) - Riama Vensya Sitohang (CV. Get Press Indonesia, 2026)
This study aims to analyze the resilience of health systems in responding to Public Health Emergencies of International Concern (PHEIC) and to identify key determinants influencing system capacity. A mixed methods approach with an explanatory sequential design was employed, integrating quantitative and qualitative analyses. Quantitative data were derived from secondary sources covering six health system building blocks and analyzed using descriptive statistics, paired tests, and regression analysis. A composite resilience index was also developed. Qualitative data were collected through in-depth interviews with key stakeholders and analyzed thematically to contextualize quantitative findings. The results indicate a significant decline in overall system resilience during the PHEIC phase (MD = 11.30; p < 0.001), with the largest reductions observed in health service delivery and workforce capacity. Essential health services experienced substantial disruption, particularly in chronic disease care and immunization. Post-PHEIC analysis shows a significant recovery (MD = 16.80; p < 0.001), driven mainly by improvements in health information systems and medical technology. However, workforce and service delivery components did not fully recover to pre-crisis levels. The study concludes that sustainable health system resilience requires a balanced strategy integrating absorptive, adaptive, and transformative capacities, with equal emphasis on technological advancement and human resource strengthening to ensure long-term system stability.